Entrepreneurship and digital markets - Lopes da Costa, R.; Cabral, L.; Pereira, L.; Dias, Á.; Gonçalves, R. (International Journal of Economics and Business Research, 2022)
Over the past years, the digital industry has experienced a huge transformation, impacting not only entrepreneurship, but also digital platforms. All business strategies must be rethought, with the purpose of satisfying the consumer’s needs, which are constantly changing. Entrepreneurs must adapt their products to the digital format and take advantage of the benefits that digitalisation can offer, especially in a context in which markets are more dynamic and uncertain. This research aimed to comprehend how entrepreneurship and digital platforms are related, identifying the main challenges. In this sense, three research questions were formulated, based on the literature review and, a questionnaire was applied. After combining a quantitative and qualitative analysis, it was possible to realise that it is essential to take into account that digitalisation requires a rethinking of the companies strategies. Thus, entrepreneurs should take advantage of this opportunity to sell their products through these platforms.